2017
DOI: 10.5888/pcd14.160434
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department–Initiated Tobacco Control: Update of a Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: IntroductionA 2012 systematic review and meta-analysis of randomized controlled trials on emergency department–initiated tobacco control (ETC) showed only short-term efficacy. The aim of this study was to update data through May 2015.MethodsAfter registering the study protocol on the international prospective register of systematic reviews (PROSPERO) in May 2015, we searched 7 databases and the gray literature. Our outcome of interest was the point prevalence of tobacco-use abstinence at 1-month, 3-month, 6-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…A follow-up study of 778 low-income emergency department patients found that patients in the intervention group, who received a brief intervention, 6 weeks of nicotine replacement therapy, referral to a quitline had significantly higher rates of biochemically confirmed abstinence at 3 months (12.2%) compared to those who only received a brochure (4.9%). An updated meta-analysis containing 11 studies (10 published studies, 1 abstract) found a significant effect on the 1-year combined point prevalence of (RR of 1.40 (95% CI 1.06–1.86) ( P = 0.02) [ 64 ]. Together, these results suggest that the ED provides a teachable moment about the relationship between a patients symptoms and his or her tobacco use, which can lead to sustained changes in tobacco-related behaviors.…”
Section: Ed Interventions For Tobaccomentioning
confidence: 99%
“…A follow-up study of 778 low-income emergency department patients found that patients in the intervention group, who received a brief intervention, 6 weeks of nicotine replacement therapy, referral to a quitline had significantly higher rates of biochemically confirmed abstinence at 3 months (12.2%) compared to those who only received a brochure (4.9%). An updated meta-analysis containing 11 studies (10 published studies, 1 abstract) found a significant effect on the 1-year combined point prevalence of (RR of 1.40 (95% CI 1.06–1.86) ( P = 0.02) [ 64 ]. Together, these results suggest that the ED provides a teachable moment about the relationship between a patients symptoms and his or her tobacco use, which can lead to sustained changes in tobacco-related behaviors.…”
Section: Ed Interventions For Tobaccomentioning
confidence: 99%
“…In sum, exposure to tobacco is a significant problem in this population, and an alarming burden of disease is attributable to tobacco alone. 24 The WHO Tobacco Free Initiative highlights the role for brief tobacco interventions in healthcare settings, which have demonstrated effectiveness in US-based ED populations, 5 but there are no studies to date on interventions in an African ED.…”
Section: Discussionmentioning
confidence: 99%
“…More than 4 million visits to emergency departments (EDs) annually involve treatment of children with complaints that are potentially related to tobacco smoke exposure (TSE) 1 . Over 30% of children who visit the pediatric ED (PED) for TSE-related illnesses live with parents who smoke 2,3 . The economic costs attributable to lost productivity due to smoking and TSE are estimated to be $190.7 billion and $7.2 billion, respectively.…”
Section: Introductionmentioning
confidence: 99%